Agile HRM Practices : A Strategic Approach to Adapting to Technological Disruptions and Workforce Dynamics - Gowrishankkar, Vijayan; Bhavani, Jay; Vijay, B; Maruthamuthu, Murugesan; Palanivel Rathinasabapathi, Velmurugan; Vimala, Govindaraju (IGI Global Scientific Publishing, 2024)
In today’s fast-paced business environment, organizations must be agile to remain competitive, and Agile Human Resource Management has emerged as a key enabler of this adaptability. This manuscript explores the transformative shift from traditional human resource management models to agile human resource management models, a flexible and iterative approach that emphasizes continuous improvement, collaboration, and alignment with organizational strategies. Agile human resource management models plays a critical role in responding to technological advancements, global competition, and evolving workforce dynamics, such as remote work and multi-generational teams. By leveraging digital tools and promoting a culture of continuous learning, agile human resource management models foster innovation, employee engagement, and organizational resilience. This study examines the principles of agile human resource management models, its evolution from traditional practices, and its practical applications in modern business contexts.